Molecular Evolution of the Influenza A Virus Non-structural Protein 1 in Interspecies Transmission and Adaptation - Evseev, Danyel; Magor, Katharine E. (Frontiers in Microbiology, 2021)
The non-structural protein 1 (NS1) of influenza A viruses plays important roles in viral fitness and in the process of interspecies adaptation. It is one of the most polymorphic and mutation-tolerant proteins of the influenza A genome, but its evolutionary patterns in different host species and the selective pressures that underlie them are hard to define. In this review we highlight some of the species-specific molecular signatures apparent in different NS1 proteins and discuss two functions of NS1 in the process of viral adaptation to new host species. First, we consider the ability of NS1 proteins to broadly suppress host protein expression through interaction with CPSF4. This NS1function can be spontaneously lost and regained through mutation and must be balanced against the need for host co-factors to aid efficient viral replication. Evidence suggests that this function of NS1 may be selectively lost in the initial stages of viral adaptation to some new host species. Second, we explore the ability of NS1 proteins to inhibit antiviral interferon signaling, an essential function for viral replication without which the virus is severely attenuated in any host. Innate immune suppression by NS1 not only enables viral replication in tissues, but also dampens the adaptive immune response and immunological memory. NS1 proteins suppress interferon signaling and effector functions through a variety of protein-protein interactions that may differ from host to host bust much achieve similar goals. The multifunctional influenza A virus NS1 protein is highly plastic, highly versatile, and demonstrates a diversity of context-dependent solutions to the problem of interspecies adaptation.